Filmowość Marii Antoniego Malczewskiego - Sławnikowski, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The aim of this article is to analyse the poetics of Antoni Malczewski’s Maria in terms of its cinematic qualities. The author uses various film theories, including those formulated by Siegfried Kracauer, Béla Balázs and Jean Mitry, in order to approximate the meaning of a text being cinematic and to find tools for the analysis of a literary text through this lens. Six features are distinguished: (1) fragmentariness of the plot structure, (2) editing within scenes, (3) a focus on movement, (4) transcending the limitations of human perception, (5) quasi-reproduction of reality and (6) giving images meaning as parts of a larger composition. These can be found in different passages from Maria, the analysis of which leads the author to conclude that the key to the cinematic qualities in Malczewski’s novel is the quasi-impersonal reproduction of reality achieved thanks to the withdrawn narrative perspective, the descriptions of empirical reality and the behavioural characteristics of the characters. In the summary, the cinematic qualities of Maria are put within a context of the history of literature and linked to the break with classicistic poetics and the move towards Romanticism.